(untitled) (Issues in Social and Environmental Accounting (ISEA), 2013)
The objective of this study is to examine the impact of work ethics on performance using job satisfaction and affective commitment as mediating variables. The variables used include the dimensions of multidimensional work ethic profile (independent variable), job satisfaction and affective commitment (mediating variables), and performance (dependent variable). The sur vey research design was applied to meet the objective of this study, with 400 questionnaires had been sent to the lecturers in Central Java. The Structural Equation Model (SEM) was adopted to test some hypotheses developed in this study. The findings, based on the response rate of 76% (304 of the 400) of the questionnaires successfully collected and ready for analy sis, are that not all dimensions of multidimensional work ethic profile directly influence the task performance, of the dimensions of multidimensional work ethic profile, only the dimen sion of hard work directly and significantly influence the task performance, job satisfaction mediates some of the dimensions of multidimensional work ethic profile on the task perform ance, and affective commitment do not mediate the influence of all dimensions of multidimen sional work ethic profile on the task performance.